VR game - Ong, Rui Peng (Nanyang Technological University, 2022)
Virtual Reality (VR) has many applications and one of them is gaming. The number of VR games in comparison to games such as PC games are little. By developing a VR game, consumers are presented with more choices of selection. This report discusses a VR game that is a first-person shooter castle defense. A game design document is written to flesh out its game mechanics and gameplay. The implementation of the core mechanics of the game are also documented.